UJI KETAHANAN VARIETAS PADI LOKAL JAWA BARAT DAN RESPONNYA TERHADAP PEMBERIAN GIBERELIN PADA KONDISI CEKAMAN RENDAMAN SEBAGAI UPAYA PENINGKATAN PRODUKSI DI LAHAN RAWAN BANJIR - Lia Sugiarti; Kovertina Rakhmi Indriana; Roni Assafaat Hadi (Jurnal Agroekoteknologi, 2017)
This research was aimed to examines the effect of gibberellin concentration on germination, growth and yield components of rice varieties in flood prone areas. Based on the objective, the nature of this research was verification by experimental approach in screen house and in the field. The research was conducted in the screen house and in the field of production garden of the Faculty of Agriculture of Winaya Mukti Tanjungsari - Sumedang, with a height of 850 m asl. Experiments used Randomized Completely Block Design as factorial pattern, which consisted of two factors namely four levels of gibberellin concentration and five levels of local rice varieties of West Java. Each treatment was repeated twice, then the total amount: 4 x 5 x 2 = 40 plots. Based on the results of research and discussion that had been described in the previous, it could be drawn conclusions on germination, growth and yield components of flood prone land, including: (1) there was an interaction between the various local rice varieties of West Java and the level of gibberellin concentration to the inundation stress on the ratio of root dump at age 40 day after planting, (2) the concentration of gibberellin 10 mg.L-1 gave the best results on observations for each local varieties of egypt and varieties Mareum on the root-to-dose ratio of 40 days after planting and Varieties of rice plants independently effect the number of sprouts aged day after planting, seed vigor, root length of roots, plant height 40 days after planting, and number of tillers per hump of 40 days after planting.Keywords: Rice varieties, Flooded plains, Giberelin acid